THE EFFECTIVENESS OF CATEGORIES GAMES IN TEACHING VOCABULARY - Husnul Khotimah; I Made Permadi Utama (Universitas Islam Lamongan, 2018)
The aim of this research is to find out whether Categories Games is effective or not in teaching vocabulary to the second grade students of SMAN 1 Sikur. This research was True Experimental with posttest-only control design. The object of this research was second grade students of SMAN 1 Sikur. The total numbers of population were 150 students. The technique to take the sample was cluster random sampling, which took 40 students as the sample in this research. At the first time, the researcher gave Pre test to the experimental and control group. The second time, the researcher gave the treatment that used Categories Games in experimental group and Puzzle Game in control group, then the last, the researcher gave post test both of group. From the data is obtained, it found that T-test was 6,96 and t-table at significance level of 0,05 (95%) was 2,02. So it means that the score of t-test was higher than t-table (6,96 > 2.02). The alternate hypothesis (Ha), which used Categories Games in teaching vocabulary to the second grade of SMAN 1 Sikur was effective absolutely accepted. Meanwhile, the Null Hypothesis (Ho), which used Categories Games in teaching vocabulary to the second grade of SMAN 1 Sikur is not effective is absolutely rejected. Effectiveness of Categories Games was suitable for teaching vocabulary beside that practicable and applicable for English subject especially in teaching vocabulary